What is the importance of islands to environmental conservation? - KUEFFER, CHRISTOPH; KINNEY, KEALOHANUIOPUNA (Environmental conservation, 2017)
This article discusses four features of islands that make them places of special importance to environmental conservation. First, investment in island conservation is both urgent and cost-effective. Islands are threatened hotspots of diversity that concentrate unique cultural, biological and geophysical values, and they form the basis of the livelihoods of millions of islanders. Second, islands are paradigmatic places of human–environment relationships. Island livelihoods have a long tradition of existing within spatial, ecological and ultimately social boundaries and are still often highly dependent on local resources and social cohesion. Island cultures and their rich biocultural knowledge can be an important basis for revitalizing and innovating sustainable human–nature relationships. Third, islands form a global web that interlinks biogeographic regions and cultural spaces. They are nodes in a global cultural network: as multicultural island societies, through diaspora islander communities on continents and through numerous political and trade relationships among islands and between islands and countries on continents. Fourth, islands can serve as real-world laboratories that enable scientific innovation, integration of local and generalized knowledge and social learning and empowerment of local actors. We conclude that island systems can serve as globally distributed hubs of innovation, if the voices of islanders are better recognized.